Neointimal tissue component assessed by tissue characterization with 40 MHz intravascular ultrasound imaging: Comparison of drug‐eluting stents and bare‐metal stents. Issue 7 (27th March 2013) - Tsujita, Kenichi; Takaoka, Naoko; Kaikita, Koichi; Hokimoto, Seiji; Horio, Eiji; Sato, Koji; Mizobe, Michio; Nakayama, Naoki; Kojima, Sunao; Tayama, Shinji; Sugiyama, Seigo; Nakamura, Sunao; et al.
<x xml:space="preserve">Abstract</x> Objectives The present study used iMap IVUS system to compare neointimal tissue components between DES and bare‐metal stents (BMSs). Background Drug‐eluting stents (DESs) can cause impaired arterial healing, which constitutes the most important pathological substrate underlying late DES thrombosis. Intravascular ultrasound (IVUS)‐based tissue characterization allows for the in vivo identification of neointimal tissue components. Methods and Results Follow‐up IVUS data after coronary stenting (9.8 ± 9.4 months from index procedures) was obtained from consecutive 61 lesions (34 in DES, 27 in BMS). The iMap tissue components (fibrotic, lipidic, necrotic, and calcified) were measured in every recorded frame and expressed as percentages of mean neointimal cross‐sectional area for the stented segment. Patients' characteristics were comparable between DES and BMS. When compared with BMSs, smaller (2.9 ± 0.4 mm vs. 3.2 ± 0.4 mm, P = 0.004) and longer (34 ± 18 mm vs. 26 ± 14 mm, P = 0.03) DESs were implanted. When compared with BMS group, minimum lumen area at follow‐up was significantly greater in DES group (3.9 ± 1.8 mm2 vs. 3.1 ± 1.5 mm2, P < 0.04), mainly attributable to suppression of neointimal hyperplasia (1.7 ± 0.8 mm2 vs. 3.1 ± 1.5 mm2, P < 0.0001). The iMap analyses showed that neointima after DES placement was composed of smaller fibrotic component (67 ± 8% vs. 78 ± 7%, P < 0.0001), larger necrotic (14 ± 4% vs. 9 ± 3%, P < 0.0001) and calcified (15 ± 6% vs. 7 ± 4%, P < 0.0001) components compared with BMS. Logistic regression analysis showed that only intra‐DES neointima was a significant predictor of necrotic neointima at follow‐up. Conclusions DES implantation would be associated with iMap‐derived necrotic and less‐fibrotic neointimal formation. In vivo iMap evaluation of neointimal tissue may provide useful information in detecting impaired healing after stenting. © 2013 Wiley Periodicals, Inc.